Revisiting India's growth and development - Nayak, Pulin B. (2016)
I G Patel's lifelong concern was to think about framing and implementing policies to lift India from the morass of low per capita income and low levels of social indicators to that of a country which was economically strong and one which would be able to hold its own in the comity of nations. This called for growth at a rapid pace, but, as he always emphasised, in a manner which would necessarily pay adequate attention to the welfare of the poorest sections. It was this which was his abiding concern. - Reproduced.
Keywords: Economic and social development - India; Economic growth - India; Economic growth